A clinical and histopatholgical study of nevus sebaceus - Neerja Puri (Our Dermatology Online, 2013)
Background Nevus sebaceus (NS), otherwise designated as 'organoid nevus', involves proliferative changes of the sebaceous glands, sweat glands, and the hair follicles. It displays a range of appearances, depending on the lesion's age. Aims To study the clinical features along with histopathological study of 20 cases of nevus sebaceus. Methods We selected 20 cases of nevus sebaceous for the study. Results Clinically,verrucous plaques were seen in 60% patients, papules were seen in 25% patients and patches were seen in 15% patients. All of them showed abortive/immature hair follicles characterized by cords of undifferentiated, basaloid cells resembling the embryonic stages of hair follicle. Conclusions To conclude, NS is an organoid nevus, i.e a hamartoma consisting of various elements indigenous to the organ and not merely the sebaceous units.